Functional analysis of Toll-related genes in Drosophila - Yagi, Yoshimasa (2010)
The Drosophila genome encodes a total of nine Toll and related proteins. The immune and developmental functions of Toll and 18Wheeler (18W) have been analyzed extensively, while the in vivo functions of the other Toll-related proteins require further investigation. We performed transgenic experiments and found that overexpression of Toll-related genes caused different extents of lethality and developmental defects. Moreover, 18w, Toll-6, Toll-7 and Toll-8 often caused related phenotypic changes, consistent with the idea that these four genes have more conserved molecular structure and thus may regulate similar processes in vivo. Deletion alleles of Toll-6, Toll-7 and Toll-8 were generated by targeted homologous recombination or P element excision. These mutant alleles were viable, fertile, and had no detectable defect in the inducible expression of antimicrobial peptide genes except for the Toll-8 mutant had some defects in leg development. The expression of 18w, Toll-7 and Toll-8 mRNA showed wide and overlapping patterns in imaginal discs and the 18w, Toll-8 double and Toll-7, Toll-8 double mutants showed substantially increased lethality. Overall our results suggest that some of the Toll-related proteins, such as 18W, Toll-7 and Toll-8, may have redundant functions in regulating developmental processes.